2016
DOI: 10.1103/physreva.94.043638
|View full text |Cite
|
Sign up to set email alerts
|

Supersolid phases of dipolar fermions in a two-dimensional-lattice bilayer array

Abstract: Supersolid phases as a result of a novel coexistence of superfluid and density ordered checkerboard phases are predicted to appear in ultracold Fermi molecules confined in a bilayer array of 2D square optical lattices. We demonstrate the existence of these phases within the inhomogeneous mean field approach. In particular, we show that tuning the interlayer separation distance at a fixed value of the chemical potential produces different fractions of superfluid, density ordered and supersolid phases.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Based on the current experimental advances in manipulating ultracold atoms and molecules, here we propose a model to address the study of superfluid and supersolid phases [19]. This model consist of Fermi molecules with dipole moment d and mass m lying in two parallel square lattices of lattice constant a separated by a distance λ, and a harmonic trap with frequency ω (Fig.…”
Section: Superfluid and Supersolid Phases In An Ultracold Gasmentioning
confidence: 99%
“…Based on the current experimental advances in manipulating ultracold atoms and molecules, here we propose a model to address the study of superfluid and supersolid phases [19]. This model consist of Fermi molecules with dipole moment d and mass m lying in two parallel square lattices of lattice constant a separated by a distance λ, and a harmonic trap with frequency ω (Fig.…”
Section: Superfluid and Supersolid Phases In An Ultracold Gasmentioning
confidence: 99%
“…For spinless fermions, a similar expression equation ( 77) can also be derived, yet because of the Pauli exclusion principle, the second and fourth terms of the sum in equation ( 77) cancels, only retaining the tunnelling and NNI terms. Theoretically, this case is also of interest, yet turns out to be more complicated to treat than the boson one [13,146,[739][740][741][742][743][744][745]. Few studies have shown that various kinds of charge-density-wave and SSPs also forms in dipolar fermions lattice systems in 2D [739][740][741][742]744] and 3D [743].…”
Section: Extended Hubbard Hamiltonian and Consequencesmentioning
confidence: 99%
“…Molecules can move through sites in a given layer, but they cannot tunnel between layers. Given the arrangement illustrated in Figure , several interactions between pairs can arise, such interactions being essential to define the possible phases or ordered structures as stripes or checkerboard patterns . The purpose of this work is to study the p ‐wave superfluidity emerging from attractive interactions between molecules lying in layers A and B .…”
Section: Modelmentioning
confidence: 99%
“…Given the arrangement illustrated in Fig. 1, several interactions between pairs can arise, being such interactions essential to define the possible phases or ordered structures that can be formed [22][23][24][25]. The purpose of this work is to study the p−wave superfluidity emerging from attractive interactions between molecules lying in layers A and B.…”
Section: Modelmentioning
confidence: 99%